Method for reducing stress and cracking of high-strength aluminum alloy test piece formed by additive manufacturing through laser energy balance method
By using laser energy balance method in laser additive manufacturing, the laser forming process parameters are optimized and the medium-temperature and short-term heat treatment is carried out, the problem of difficult stress deformation of high-strength aluminum alloys formed by laser additive manufacturing is solved, and the effect of suppressing internal stress and cracking is achieved, and the application range is broadened.
Patent Information
- Application Number
- CN202510100121.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Laser additive manufacturing and forming high-strength aluminum alloys are prone to generate large thermal stress during rapid laser melting and curing, resulting in stress cracking and deformation of finished products during manufacturing or use, which is difficult to control.
The laser energy balance method is adopted to optimize the laser forming process parameters, reduce the laser power and scanning speed, and ensure that the laser energy density does not change significantly, the laser forming process parameters are adjusted, the temperature gradient and inherent residual stress in the melt pool are reduced, and the medium-temperature short-term heat treatment is performed in the post-treatment to remove the internal stress.
It effectively suppresses the internal stress level and cracking tendency of the high-strength aluminum alloy specimens of additive manufacturing, ensures that the formed parts do not deform or crack, and broadens the application range of complex high-strength aluminum alloy structures for laser additive manufacturing.
Smart Images

Figure CN119910198A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of additive manufacturing, and in particular relates to a process for suppressing stress deformation cracking of high-strength aluminum alloy formed by laser additive manufacturing. Background Art
[0002] Additive manufacturing (AM), especially laser additive manufacturing (LAM), has been widely used in the aerospace industry because it can directly manufacture complex parts from digital models in a short time. This technology can effectively shorten the product development cycle, reduce material waste, and allow the design and manufacture of complex structures that are difficult to achieve with traditional methods. Especially for high-strength aluminum alloy materials, additive manufacturing technology provides a unique way to make lightweight structural parts, which is particularly important for the application of weight-sensitive complex components in the aerospace field. At present, laser additive manufacturing of high-strength aluminum alloy systems modified with trace elements such as Sc and Zr has become a research hotspot for research and development and application worldwide. First, additive manufacturing technology is expected to break through the technical bottlenecks of lightweight and integrated traditional manufacturing technology, and realize lightweight design and integrated manufacturing of complex components. Second, the trace element modified high-strength aluminum alloy system developed for additive manufacturing has broken through the problem of insufficient strength (<400MPa) caused by the single strengthening mechanism of conventional Al-Si alloys, and can further promote lightweight design while meeting high load requirements. Therefore, laser additive manufacturing of high-strength aluminum alloys has important application prospects in the fields of complex components such as aerospace, automobile transportation, etc.
[0003] However, there are still a series of technical challenges in the use of additive manufacturing technology to form complex parts of high-strength aluminum alloys. Due to the high thermal conductivity and large expansion coefficient of aluminum alloys, it is easy to generate large thermal stresses during rapid laser melting and solidification. The uneven distribution of these thermal stresses in the material often leads to stress cracking and deformation of the finished product during the manufacturing process or use, especially when manufacturing complex or large-scale structures. The problem of stress concentration not only affects the mechanical properties and precision of the parts, but may also lead to low production efficiency and material waste. At present, some attempts have been made to solve these problems through post-processing methods (such as heat treatment and stress relief), but in actual production processes, cracking and failure often occur due to stress deformation after printing, which is difficult to repair using post-processing or orthopedic technology. Therefore, the development of a new method that can effectively control the generation and distribution of stress in the additive manufacturing process is of great practical significance for improving the manufacturing quality and reliability of high-strength aluminum alloy parts.
[0004] In summary, laser additive manufacturing technology for forming high-strength aluminum alloys has great advantages in the field of forming complex aerospace structural parts, but there are still problems such as difficult to control stress deformation and cracking failure. Currently, there is no process method to effectively achieve stress and deformation control of complex components made of high-strength aluminum alloys in additive manufacturing. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is that stress deformation is difficult to control and cracking failure occurs in high-strength aluminum alloys formed by existing laser additive manufacturing. A method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method is proposed.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A method for reducing stress cracking of a high-strength aluminum alloy specimen formed by additive manufacturing using a laser energy balance method comprises the following steps:
[0008] S1. Optimization of conventional laser forming process parameters:
[0009] Determine the conventional laser forming process range for the rare earth element modified Al-Mg / Mn alloy system;
[0010] Performing a forming test of a test formed part within the determined conventional laser forming process range to obtain optimized laser forming process parameters, and calculating corresponding laser energy density η based on the optimized laser forming process parameters;
[0011] The optimized laser forming process parameters include optimized laser power, optimized scanning speed, optimized layer thickness and optimized scanning spacing;
[0012] S2. Laser energy balance method to adjust laser forming process parameters:
[0013] The optimized laser forming process parameters obtained in step S1 are adjusted by using the laser energy balance method. On the premise of ensuring that the difference in laser energy density before and after the adjustment is not significant, the optimized laser power is first reduced to the target range, and then other parameters included in the optimized laser forming process parameters are adjusted;
[0014] S3. Integrated forming of complex components:
[0015] Based on the adjusted laser forming process parameters obtained in step S2, complex component additive manufacturing integrated forming is performed to obtain a complex component formed part;
[0016] S4, medium temperature short time heat treatment:
[0017] The complex component formed part obtained in step S3 is subjected to medium-temperature short-time heat treatment to further remove internal stress, complete the overall stress relief process of the complex component formed part, and obtain a heat-treated complex component.
[0018] Preferably, in step S1, the rare earth element modified Al-Mg / Mn alloy system is any one of a rare earth element modified Al-Mg alloy, a rare earth element modified Al-Mn alloy or a rare earth element modified Al-Mn-Mg alloy.
[0019] Preferably, the rare earth element is any one of Sc, Zr, Er, and Ti, or a combination of two or more thereof.
[0020] Preferably, in step S1, the rare earth element modified Al-Mg / Mn alloy system is a rare earth element modified Al-Mn-Mg alloy, comprising the following components: Mg 7-9wt.%, Si 0.4-1.2wt.%, Mn 0.3-0.8wt.%, Sc 0.5-0.7wt.%, Zr 0.2-0.5wt.%, and the remainder is Al; in the conventional laser forming process range, the laser power is 350-450W, the scanning speed is 800mm / s-1600mm / s, the layer thickness is 30μm, and the scanning spacing is 120μm.
[0021] Preferably, in step S1, the laser energy density η is calculated according to the following formula:
[0022] η=P / (v*h*t);
[0023] In step S2, the adjusted laser forming process parameters satisfy:
[0024] δ1≤η' / η≤δ2 and P01≤P'≤P02 <P;
[0025] Wherein: η' represents the laser energy density of the adjusted laser forming process parameters; η represents the laser energy density corresponding to the laser forming process parameters optimized in step S1; δ1 represents the preset minimum allowable energy density; δ2 represents the preset maximum allowable energy density; P' represents the adjusted laser power; P01 represents the preset minimum laser power; P02 represents the preset maximum laser power; and P represents the laser power optimized in step S1.
[0026] In step S2, the preset minimum allowable energy density value δ1 is 0.85, the preset maximum allowable energy density value δ2 is 1.0; the preset minimum laser power value P01 is 200W; the preset maximum laser power value P02 is 250W; and the optimized laser power P is greater than 350W.
[0027] Preferably, in step S4, the aging temperature of the medium-temperature short-time heat treatment is controlled at 280-300° C., and the time is 2-4 hours.
[0028] Preferably, in step S1, among the optimized laser forming process parameters, the optimized laser power is 440W, and the optimized laser scanning speed is 1350mm / s; the laser energy density η' of the adjusted laser forming process parameters is 90.19, and the adjusted laser power P' is 230W, the adjusted laser scanning speed is 850mm / s, the layer thickness is 30μm, and the scanning spacing is 100μm.
[0029] Preferably, in step S4, the heat treatment heating rate is 5K / min, the heat treatment temperature is 300°C, and the heat treatment time is 2h.
[0030] Beneficial effects:
[0031] The present invention aims to regulate stress cracking of high-strength aluminum alloy formed by additive manufacturing. An isodensity process control strategy is introduced within the conventional optimized process range to ensure that the powder is fully melted, wetted and spread. At the same time, the internal stress of the original deposited specimen is reduced by lowering the molten pool temperature and temperature gradient to reduce the participating stress and inhibiting the precipitation of the primary precipitation phase caused by in-situ heat treatment.
[0032] From the perspective of physical mechanism, the internal stress and cracking of high-strength aluminum alloy specimens formed by laser additive manufacturing mainly come from two aspects. First, laser additive manufacturing has the characteristics of local rapid melting. The high temperature gradient and solidification rate will cause the atomic crystal arrangement to deviate from the equilibrium state and induce the initiation of internal stress. This is an inherent characteristic of additive manufacturing. Second, the high-strength aluminum alloy modified by trace elements is a precipitation strengthening mechanism. If the energy input is high during the forming process (generally indicating high laser power), it is easy to promote the precipitation of primary phases such as Al 3 (Sc, Zr) precipitation. At the same time, high energy input will also lead to the aggravation of the overall heat accumulation of the specimen during the forming process. The stacking effect and in-situ heat treatment effect of additive manufacturing will further promote the coarsening of the precipitate phase. These precipitates during the solidification process and subsequent stacking manufacturing are mainly distributed at the grain boundaries. On the one hand, it will weaken the grain boundary strength to form local stress concentration; at the same time, the precipitates will also hinder the dislocation movement and reduce the plastic toughness of the specimen. Therefore, under the action of internal stress caused by the inherent characteristics of additive manufacturing, the high-strength aluminum alloy modified by trace elements formed by additive manufacturing is prone to deformation and cracking failure due to internal stress concentration.
[0033] Therefore, in order to reduce the internal stress and cracking phenomenon of the trace element modified high-strength aluminum specimens formed by additive manufacturing, it is necessary to start from the following two aspects: one is to reduce the inherent internal stress level of the additive manufacturing process as much as possible, and the other is to inhibit the precipitation and coarsening of the primary precipitation phase during the forming process.
[0034] The present invention proposes to introduce an equal density process control strategy (i.e., laser energy balance method) under the premise of optimizing the conventional laser forming process interval, and to reduce the temperature gradient of the laser additive manufacturing molten pool under the premise of basically no significant change in laser energy density by synergistically reducing the optimized laser power and the optimized scanning speed, thereby achieving the purpose of reducing the internal stress of the trace element modified high-strength aluminum specimen and inhibiting the cracking phenomenon of the trace element modified high-strength aluminum specimen. Specifically, the present invention reduces the optimized laser power under the premise of ensuring that there is no significant difference in the laser energy density before and after the adjustment of the optimized laser forming process parameters, and ensures that the energy input by the reduced laser power can melt and wet the molten pool. Therefore, on the one hand, reducing the laser power can reduce the temperature gradient and inherent residual stress in the molten pool. On the other hand, reducing the laser power reduces the heat input of the molten pool, which can inhibit the coarsening and growth process of the primary precipitation phase, and then inhibit the intergranular cracking behavior caused by local stress concentration. At the same time, in the post-treatment stress relief process, the "medium temperature and short time" process strategy is adopted to avoid the cracking behavior caused by the significant coarsening of the precipitation phase at the grain boundary.
[0035] The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using the laser energy balance method proposed in the present invention can effectively suppress the internal stress level and cracking tendency in situ during the forming process of trace element modified high-strength aluminum alloy, ensure that no deformation gauge cracking occurs in the formed part under the original deposition state, broaden the application of laser additive manufacturing of complex high-strength aluminum alloy structures, and has strong operability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0037] Figure 1 The process flow chart of the method of the present invention is shown in FIG.
[0038] Figure 2 Schematic diagram of the effect of equal-density process control on microstructure.
[0039] Figure 3 This is a macroscopic image of the formed component of Example 3 in the specific embodiment.
[0040] Specific implementation method Figure 1 The method of reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method of the present invention comprises the following steps:
[0041] S1. Optimization of conventional laser forming process parameters:
[0042] Determine the conventional laser forming process range for the rare earth element modified Al-Mg / Mn alloy system;
[0043] Conduct forming tests on the test forming parts within the determined conventional laser forming process range to obtain optimized laser forming process parameters, and calculate the corresponding laser energy density η based on the optimized laser forming process parameters;
[0044] The optimized laser forming process parameters include optimized laser power, optimized scanning speed, optimized layer thickness, and optimized scanning spacing. Generally, however, when conducting forming tests in a wide process range of the test forming parts, optimization is carried out for the laser power and scanning speed, while the layer thickness and scanning spacing are generally selected as fixed values.
[0045] In the present invention, for the laser additive manufacturing forming process, its laser energy density η is calculated according to the following formula: η = P / (v * h * t), where: P represents the laser power; v represents the scanning speed; h represents the scanning spacing; t represents the layer thickness.
[0046] S2. Adjust the laser forming process parameters by the laser energy balance method:
[0047] Adopt the laser energy balance method to adjust the optimized laser forming process parameters obtained in step S1. On the premise of ensuring that the difference in laser energy density before and after adjustment is not significant, first reduce the optimized laser power to the target range, and then adjust the other parameters included in the optimized laser forming process parameters.
[0048] In fact, in this step, it is necessary to协同 reduce the optimized laser power and optimized scanning speed determined in step S1, and based on the calculation formula of the laser energy density, adjust the optimized layer thickness and optimized scanning spacing determined in step S1.
[0049] The adjusted laser forming process parameters need to meet two conditions. One condition is the condition of no significant difference in laser energy density (that is, the laser energy density before and after adjustment needs to be maintained in a "balanced" state): δ1 ≤ η’ / η ≤ δ2. The other condition is that the heat provided by the adjusted laser power only needs to meet the requirements of melting and wetting the molten pool: P01 ≤ P’ ≤ P02 < P. Where: η’ represents the laser energy density of the adjusted laser forming process parameters; η represents the laser energy density corresponding to the optimized laser forming process parameters in step S1; δ1 represents the preset minimum allowable value of the energy density, and the value can be 0.85; δ2 represents the preset maximum allowable value of the energy density, and the value can be 1.0; P’ represents the adjusted laser power; P01 represents the preset minimum value of the laser power, and the value can be 200W; P02 represents the preset maximum value of the laser power, and the value can be 250W; P represents the optimized laser power in step S1, and the value is generally greater than 350W.
[0050] S3. Integral forming of complex components:
[0051] Based on the adjusted laser forming process parameters obtained in step S2, complex component additive manufacturing integrated forming is carried out to obtain a complex component formed part.
[0052] S4, medium temperature short time heat treatment:
[0053] The complex component formed part obtained in step S3 is subjected to medium-temperature short-time heat treatment to further remove internal stress, complete the overall stress relief process of the complex component formed part, and obtain a heat-treated complex component.
[0054] The present invention can be better understood with reference to the following examples.
[0055] Example 1
[0056] Step 1: Optimization of conventional laser forming process parameters:
[0057] In this embodiment, an alloy system with precipitation strengthening characteristics and good laser powder bed melt formability is preferred. The rare earth element modified Al-Mg / Mn alloy system is selected as Al-Mg-Mn-Si alloy, wherein the alloy components are Mg 7-9wt.%, Si 0.4-1.2wt.%, Mn 0.3-0.8wt.%, Sc 0.5-0.7wt.%, Zr 0.2-0.5wt.%, and the balance is Al. The raw material is spherical alloy powder with a powder particle size of 15-45μm and D 50 ≥25μm. The powder is dry and has good fluidity.
[0058] In this embodiment, for the above-mentioned Al-Mg-Mn-Si alloy, laser additive manufacturing forming equipment was used to carry out process tests and determine the process window. Forming tests within a wide process range were carried out using a laser power of 350-450W, a scanning speed of 800mm / s-1600mm / s, a layer thickness of 30μm, and a scanning interval of 120μm.
[0059] The density of the formed test block was tested using the Archimedes drainage method, and the optimized process parameters were a process combination of laser power 440W and laser scanning speed 1350mm / s, with a forming density greater than 99.5%.
[0060] In other words, this step first determines the conventional laser forming process range for Al-Mg-Mn-Si alloy: laser power 350-450W, scanning speed 800mm / s-1600mm / s, layer thickness 30μm, scanning spacing 120μm; then the conventional laser forming process range is used to carry out the forming test of the test formed part to optimize the laser power and scanning speed, and obtain the corresponding laser power optimization value of 440W and scanning speed optimization value of 1350mm / s, and then calculate the laser energy density as η=P / (v*h*t)=440 / (1.35*10 3 *30*10 -6 *120*10 -6 )=90.53J / m 2 .
[0061] Step 2: Adjust laser forming process parameters using the laser energy balance method:
[0062] The laser energy balance method is used to perform parameter scaling calculation. Specifically, since the adjusted laser power P' needs to satisfy 200≤P'≤250, the laser power can be adjusted to 230W, considering the energy density ratio 0.85≤η 后 / η 前 ≤1.0, set the laser scanning speed to 850mm / s, layer thickness to 30μm, scanning spacing to 100μm, then η 后 =230 / (850*10 3 *30*10 -6 *100*10 -6 )=90.19J / m 2 , then η 后 / η 前 =0.996, which meets the aforementioned condition that there is no significant difference in laser energy density.
[0063] It can be seen that this step is based on the laser energy balance method, which synergistically reduces the laser power optimization value and scanning speed optimization value obtained in step two, and is supplemented by adjusting the scanning spacing, so that the laser forming process parameters before and after adjustment basically meet the "equal density scaling" principle.
[0064] Step 3: Based on the process parameters after isodensity scaling, conduct laser additive manufacturing forming tests. Test the density of the formed specimens and the cracking of large-sized specimens. The density of the formed specimens can be found in Table 1.
[0065] Step 4: Perform medium temperature short-time heat treatment on the formed specimens using an atmosphere heat treatment furnace. The heat treatment heating rate is 5K / min, the heat treatment temperature is 300°C, and the heat treatment time is 2h. After treatment, the mechanical properties and cracking of the formed parts are tested. For details, please refer to Table 1.
[0066] Figure 2 This is a schematic diagram of the laser energy balance method of the present invention to reduce the impact of additive manufacturing on the microstructure of high-strength aluminum alloy. Through the adjustment of the isodensity process, the size and number of primary precipitates inside the formed specimen are significantly reduced, which can significantly inhibit the stress concentration and cracking behavior caused by grain boundary precipitates. There is no deformation and cracking after forming and processing. The stress and deformation of the trace element modified high-strength aluminum alloy formed by laser additive manufacturing are significantly suppressed.
[0067] Example 2
[0068] The difference between this embodiment and embodiment 1 is that: in step 2, the ratio η is controlled 后 / η 前 =0.982; the laser process forming parameters after iso-density scaling are: laser power 200W, scanning speed 750mm / s, layer thickness 30μm, scanning spacing 100μm, at this time η 后 =88.88, and the rest is the same as in Example 1.
[0069] The components were formed by using laser process forming parameters after equal density scaling. The obtained laser formed components were subjected to density testing. The test results can be referred to Table 1.
[0070] The mechanical properties and cracking conditions of the laser-formed components obtained after medium-temperature short-time heat treatment can be found in Table 1.
[0071] Example 3
[0072] The difference between this embodiment and embodiment 1 is that: in step 2, the ratio η is controlled 后 / η 前 =0.85; the laser process forming parameters after iso-density scaling are: laser power 200W, scanning speed 1150mm / s, layer thickness 30μm, scanning spacing 100μm, at this time η 后 =76.95, and the rest is the same as in Example 1.
[0073] The components were formed by using laser process forming parameters after equal density scaling. The obtained laser formed components were subjected to density testing. The test results can be referred to Table 1.
[0074] The mechanical properties and cracking conditions of the laser-formed components obtained after medium-temperature short-time heat treatment can be found in Table 1.
[0075] Example 4
[0076] The difference between this embodiment and embodiment 1 is that: in step 2, the ratio η is controlled 后 / η 前=0.90; the laser process forming parameters after iso-density scaling are: laser power 230W, scanning speed 1350mm / s, layer thickness 30μm, scanning spacing 47.8μm, at this time η 后 =81.47, and the rest is the same as in Example 1.
[0077] The components were formed by using laser process forming parameters after equal density scaling. The obtained laser formed components were subjected to density testing. The test results can be referred to Table 1.
[0078] The mechanical properties and cracking conditions of the laser-formed components obtained after medium-temperature short-time heat treatment can be found in Table 1.
[0079] Example 5
[0080] The difference between this embodiment and embodiment 1 is that the test piece is formed in step 1, and there is no subsequent equal density process adjustment process in step 2 and step 3; the heat treatment process in step 4 is the same as that in embodiment 1.
[0081] Figure 3 This is the specimen formed in Example 5. After forming and processing, cracking was found. Therefore, we can believe that with conventional forming parameters, the laser additive manufacturing trace element modified high-strength aluminum alloy specimen has greater stress and cracking tendency inside.
[0082] Example 6
[0083] The difference between this embodiment and embodiment 1 is that: in step 2, the ratio η is controlled 后 / η 前 =1.1, and the laser process forming parameters after equal density scaling are: laser power is 240W, laser scanning speed is set to 800mm / s, layer thickness is 30μm, scanning spacing is 100μm, and the others are the same as Example 1.
[0084] The components were formed by using laser process forming parameters after equal density scaling. The obtained laser formed components were subjected to density testing. The test results can be referred to Table 1.
[0085] The mechanical properties and cracking conditions of the laser-formed components obtained after medium-temperature short-time heat treatment can be found in Table 1.
[0086] Figure 3 This is the test piece formed in Example 3. After forming and processing, cracking was found. With conventional forming parameters, the laser additive manufacturing formed trace element modified high-strength aluminum alloy test piece has greater stress and cracking tendency inside.
[0087] Example 7
[0088] The difference between this embodiment and embodiment 1 is that: in step 2, the ratio η is controlled后 / η 前 =0.81, the laser process forming parameters after iso-density scaling are: laser power is 220W, laser scanning speed is set to 1000mm / s, layer thickness is 30μm, scanning spacing is 100μm, at this time η 后 =73.33, and the rest is the same as in Example 1.
[0089] The components were formed by using laser process forming parameters after equal density scaling. The obtained laser formed components were subjected to density testing. The test results can be referred to Table 1.
[0090] The mechanical properties and cracking conditions of the laser-formed components obtained after medium-temperature short-time heat treatment can be found in Table 1.
[0091] Example 8
[0092] The difference between this embodiment and embodiment 1 is that the heat treatment temperature in step 4 is 350° C., and the rest is the same as embodiment 1.
[0093] Example 9
[0094] The difference between this embodiment and embodiment 1 is that the heat treatment time in step 4 is 6 hours, and the rest is the same as embodiment 1.
[0095] The density, mechanical properties and complex component forming tests were performed on the formed specimens under different embodiments. The test results of different embodiments are shown in Table 1.
[0096] Table 1 Quality of high-strength aluminum alloy specimens formed in different embodiments
[0097]
[0098]
[0099] From Table 1 we can see that:
[0100] Comparing Examples 1-4 with Example 5, when conventional process methods are used, it is shown that the present method has a good effect on the internal stress regulation and crack suppression of the trace element modified high-strength aluminum alloy formed by laser additive manufacturing.
[0101] Comparing Example 1 with Example 6, when the process is scaled up, the energy density is too high, which easily leads to a decrease in density and a significant decrease in tensile strength. This is because the high energy density causes the evaporation of the Mg element and the increase in the number of pores, which leads to a decrease in the density of the formed specimen and a decrease in the mechanical properties.
[0102] Comparing Example 1 with Example 7, when the energy density is too low after process scaling, the density and tensile strength will also be reduced. This is because the unfused pores between layers increase due to the low energy density, resulting in reduced density and mechanical properties of the formed specimen.
[0103] Comparing Example 1 with Example 8, when the heat treatment temperature is too high at 350°C, the density of the formed specimen is good, but the strength is reduced, and cracking occurs in the formed specimen. This is because the excessively high heat treatment temperature causes the precipitates at the grain boundaries to coarsen significantly, thereby inducing local stress concentration and cracking.
[0104] Comparing Example 1 with Example 9, when the heat treatment temperature is too long for 6 hours, the density of the formed specimen is good, but the strength is reduced, and the formed specimen cracks. This is because the excessive heat treatment time causes the precipitates at the grain boundaries to coarsen significantly, thereby inducing local stress concentration and cracking.
[0105] The present invention provides a method and idea for regulating the stress and cracking of laser additively formed trace element modified high-strength aluminum alloy through process strategy. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. A method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method, characterized in that: The steps include: S1. Optimization of conventional laser forming process parameters: Determine the conventional laser forming process range for the rare earth element modified Al-Mg / Mn alloy system; Performing a forming test of a test formed part within the determined conventional laser forming process range to obtain optimized laser forming process parameters, and calculating corresponding laser energy density η based on the optimized laser forming process parameters; The optimized laser forming process parameters include optimized laser power, optimized scanning speed, optimized layer thickness and optimized scanning spacing; S2. Laser energy balance method to adjust laser forming process parameters: The optimized laser forming process parameters obtained in step S1 are adjusted by using the laser energy balance method. On the premise of ensuring that the difference in laser energy density before and after the adjustment is not significant, the optimized laser power is reduced to the target range, and then other parameters included in the optimized laser forming process parameters are adjusted; S3, integrated forming of complex components: Based on the adjusted laser forming process parameters obtained in step S2, complex component additive manufacturing integrated forming is performed to obtain a complex component formed part; S4, medium temperature short time heat treatment: The complex component formed part obtained in step S3 is subjected to medium-temperature short-time heat treatment to further remove internal stress, complete the overall stress relief process of the complex component formed part, and obtain a heat-treated complex component.
2. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using the laser energy balance method according to claim 1 is characterized in that: In step S1, the rare earth element modified Al-Mg / Mn alloy system is any one of rare earth element modified Al-Mg alloy, rare earth element modified Al-Mn alloy or rare earth element modified Al-Mn-Mg alloy.
3. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using the laser energy balance method according to claim 2, characterized in that: The rare earth element is any one of Sc, Zr, Er and Ti or a combination of two or more thereof.
4. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method according to claim 2, characterized in that: In step S1, the rare earth element modified Al-Mg / Mn alloy system is a rare earth element modified Al-Mn-Mg alloy, including the following components: Mg 7-9wt.%, Si 0.4-1.2wt.%, Mn 0.3-0.8wt.%, Sc 0.5-0.7wt.%, Zr 0.2-0.5wt.%, and the balance is Al; in the conventional laser forming process range, the laser power is 350-450W, the scanning speed is 800mm / s-1600mm / s, the layer thickness is 30μm, and the scanning spacing is 120μm.
5. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method according to claim 4, characterized in that: In step S1, the laser energy density η is calculated according to the following formula: η=P / (v*h*t); In step S2, the adjusted laser forming process parameters satisfy: δ1≤η' / η≤δ2 and P01≤P'≤P02 <P; Where: η' represents the laser energy density of the adjusted laser forming process parameters; η represents the laser energy density corresponding to the laser forming process parameters optimized in step S1; δ1 represents the preset minimum allowable energy density; δ2 represents the preset maximum allowable energy density; P' represents the adjusted laser power; P01 represents the preset minimum laser power; P02 represents the preset maximum laser power; P represents the laser power optimized in step S1.
6. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method according to claim 5, characterized in that: In step S2, the preset minimum allowable energy density value δ1 is 0.85, the preset maximum allowable energy density value δ2 is 1.0; the preset minimum laser power value P01 is 200W; the preset maximum laser power value P02 is 250W; and the optimized laser power P is greater than 350W.
7. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method according to claim 5, characterized in that: In step S4, the aging temperature of the medium temperature short time heat treatment is controlled at 280-300°C and the time is 2-4h.
8. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method according to claim 7, characterized in that: In step S1, among the optimized laser forming process parameters, the optimized laser power is 440W, and the optimized laser scanning speed is 1350mm / s; the laser energy density η' of the adjusted laser forming process parameters is 90.19, and the adjusted laser power P' is 230W, the adjusted laser scanning speed is 850mm / s, the layer thickness is 30μm, and the scanning spacing is 100μm.
9. The method for reducing stress cracking of high-strength aluminum alloy specimens formed by additive manufacturing using a laser energy balance method according to claim 8, characterized in that: In step S4, the heat treatment heating rate is 5K / min, the heat treatment temperature is 300°C, and the heat treatment time is 2h.
Citation Information
Patent Citations
Adding material manufacturing process for aluminum alloy member
CN107881385A
Method for improving formability of high-strength aluminum alloy powder for 3D printing
CN111360257A
Process method for forming high-density and high-specific-gravity 98W alloy through double-laser following printing additive manufacturing technology
CN118893219A
Preparation method of Al-Mg-Sc-Zr alloy based on selective laser melting forming
CN119307761A
Fine-scale temporal control for laser material processing
US20170144253A1